Simulation Research on the Smooth Operation of Heavy-haul Train Based on Multi-particle Model - ZHOU Huangbiao; DU Kaibing; LUO Yuan; ZHANG Zhengfang; GUO Wei; LI Cheng (Kongzhi Yu Xinxi Jishu)
With the increase of length and weight of a heavy-haul train, longitudinal impact inside the train is also increasing to ensure the stability and safety of autonomous driving. This paper firstly compares the calculated results of the established multi-particle heavy-haul train longitudinal dynamics model under starting condition and normal operating condition with real train operating data, and the calculated results are in good agreement with the real data. Then, a simulation study is carried out on a “3+0” marshalling train with 108 heavy freight vehicles, including working conditions and effects of traction force variation on impulse of train. The results show that it is best to start a train at a uniform rate under the starting condition; in the condition of switching from traction to braking in a “fish-back” type variable ramp, the effect of switching to electric braking is best when 1/3 of the train (front part) is on the downhill and the train has the least impulse(that is, electric braking is applied as much as possible after 1/3~2/3 of the train passing through the top of the slope), and the effect of switching to air braking is best when 2/3 of the train (front part) is on the downhill( that is, air braking should be applied as much as possible after 2/3 of the train passes the slope top).